Development of Business Strategies of PT Aquanest Archipelago (Seawater Ornamental Fish & Coral Reff Trading Company) - Adamapramudita Gilrandy, Vicky; Larso, Dwi (The Indonesian Journal of Business Administration, 2016)
Abstract - PT.Â  Aquanest is an ornamental fish and coral reefs export trading company in Indonesia.Â  Since its establishment in 2012 until now, PT.Â  Aquanest has been successfully exporting the 3000 pieces ornamental fishes and 4500 pieces coral reefs to 10 countries in the world such as the United States, Brazil, Germany, England, Austria, Brazil, Greece, Iran, Malaysia and Singapore.Â  In the process, the company find significant sales gap trend each year. There are high season sales between november to april and low season sales between May to September.Â  Company analyzed, the caused of this matter it is influenced by the condition of the season in the country, where the biggest market is the United States and European countries. Therefore, PT.Â  Aquanest tries to make solution for low season sales by expanding in domestic market whichÂ  is not affected by the conditions of the season.Â  It means that companies must be provide the consumer basic needs in this business.Â  The company decided to create a retail division that sells four main products which is livestocks, equipments, maintenance supply and ready-system aquarium. On Six month after store launching, the sales did not have significant growth and tend to be low. The worst is ready-system aquarium product which is not sales at all.To fix this problem, company needs determine the best business strategy to increase the ready-systems aquarium products sales. After analyzing Companyâ€™s external and internal environment, differentiation strategies are the fittest way to achieve business performance. With using TOWS matriks, company generated several recommendation strategies. Creating aquarium project department to provide comprehensive custom aquarium from consultancy to the on-going maintenance for the clients are the main strategy to improve sales performance. This strategy will be delivered with the new business canvas model and new marketing mix. With the new value proposition â€œbring the spectacular beauty to your placeâ€, PT. Aquanest will be helped to achieve revenues target by the end of the year. To ensure the strategies is on track, business timeline is applied.Â Keywords: the ornamental fishery and coral reefs Business, business strategy, Business, Retail, Differentiation strategies, Aquanest